Livestock to 2020: the next food revolution - Delgado, Christopher L.; Rosegrant, Mark W.; Steinfeld, Henning; Ehui, Simeon; Courbois, Claude (SAGE Publications, 2001)
A revolution is taking place in global agriculture that has profound implications for human health, livelihoods and the environment. Population growth, urbanization and income growth in developing countries are fuelling a massive increase in demand for food of animal origin. These changes in the diets of billions of people could significantly improve the well-being of many rural poor. Governments and industry must prepare for this continuing revolution with long-term policies and investments that will satisfy consumer demand, improve nutrition, direct income growth opportunities to those who need them most, and alleviate environmental and public health stress.